Akses Jamban Sehat pada Balita Stunting - Wulan Angraini; Henni Febriawati; Muhammad Amin (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the relationship of ownership of access to healthy latrines to the incidence of stunting in toddlers in the Working Area of the Puskesmas Rules Mumpo, Central Bengkulu Regency. The research design used in this study was a cross-sectional study. The results showed that mothers who did not have access to restrooms did not meet the requirements of the Minister of Health Regulation Number 3 of 2014 experienced stunting toddlers as many as ten people, and mothers who had access to healthy latrines met the criteria of 8 people. Chi-square analysis found that the p-value was 0.024. In conclusion, there is a relationship between access to toilets and the incidence of stunting in toddlers in the Working Area of the Mumpo Rules Health Center, Central Bengkulu Regency. Keywords: Access to Restrooms, Toddlers, Stunting